Strategies for Addressing Teaching Challenges Among Engineering Lecturers in a South African TVET College - Mabunda, Nduvazi; Makgato, Moses; Hondonga, Jerald; Sephokgole, Daniel (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study explored strategies that can be used to address the teaching challenges faced by engineering lecturers in a selected Technical and Vocational Education and Training (TVET) college in Limpopo Province, South Africa. A qualitative research design was adopted, using semi-structured interviews and classroom observations to examine lecturers’ experiences and practices. Purposive sampling was used to select ten (n=10) lecturers who taught in the Report 191 NATED engineering programme. Data were collected through recorded interviews and observation field notes, and were analysed thematically through familiarisation with the data, coding, theme generation, theme review, and theme definition. The Pedagogical Content Knowledge (PCK) framework was used to interpret the teaching challenges experienced by engineering lecturers and the strategies used to address them. The findings identified key strategies linked to improved teaching practice, including practical lessons, online teaching, lesson preparation, communication among colleagues, and continuing professional development. The study found that the use of these strategies was uneven across participants, with important gaps in lesson preparation and the use of teaching resources. The findings suggest that TVET colleges and the Department of Higher Education and Training (DHET) should strengthen institutional support, lecturer development, and teaching infrastructure to improve teaching effectiveness in engineering education. A limitation of the study is that the Campus Management Team was not included, and future research should incorporate broader institutional perspectives.